2022
DOI: 10.3390/jcm11020298
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Water Exposure and Temperature Changes on Skin Barrier Function

Abstract: The frequency of hand hygiene has increased due to the COVID-19 pandemic, but there is little evidence regarding the impact of water exposure and temperature on skin. The aim of this study is to evaluate the effect of water exposure and temperature on skin barrier function in healthy individuals. A prospective observational study was conducted. Temperature, pH, transepidermal water loss (TEWL), erythema and stratum corneum hydration (SCH) were measured objectively before and after hot- and cold-water exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…36 A TEWL test is typically conducted to assess the integrity of the epidermal barrier, which is linked to a deficiency in the skin barrier. 37 The present study demonstrated that SHFE lotion significantly reduced transdermal water loss after 3 weeks compared with the placebo (Figure 6A). We observed a reduction in skin irritation caused by SLS exposure using a video microscope (Figure 6B).…”
Section: Discussionsupporting
confidence: 54%
“…36 A TEWL test is typically conducted to assess the integrity of the epidermal barrier, which is linked to a deficiency in the skin barrier. 37 The present study demonstrated that SHFE lotion significantly reduced transdermal water loss after 3 weeks compared with the placebo (Figure 6A). We observed a reduction in skin irritation caused by SLS exposure using a video microscope (Figure 6B).…”
Section: Discussionsupporting
confidence: 54%
“…The total amount of vapor lost through skin and appendages under non-sweating conditions from a fixed area of SC per unit of time (g/h/m 2 ) corresponds to TEWL. [35][36][37] The effect of environmental factors on TEWL values has been studied 38,39 ; however, discrepant results have been reported regarding the effect of temperature and relative humidity. 40 The results of our present work…”
Section: Discussionmentioning
confidence: 99%
“…From a different scope, cold outdoor temperatures and exposure to shampoo were associated with eczema aggravation. Currently, it remains unclear whether parabens, which are included in many daily consumer products such as cosmetics, shampoos and personal care products as preservative antimicrobial agents, induce or aggravate it [ 47 , 48 ]. However, a population study suggested an increased association between children aged 0–3 years exposed to parabens [ 49 ].…”
Section: Exposome In the Development Of Ad During Childhood And Teena...mentioning
confidence: 99%